A Study On The Method Of Teaching Reading At The Second Semester Of English Department Of Muhammadiyah University Of Surakarta In 2011/2012 Academic Year - Prihatiningsih, Dewi (2012)
The objectives of this study are (1) to describe the methods used in teaching learning process of Reading at the second semester of English Department at UMS, (2) to describe the strengths and weaknesses of the methods used by the lecturer, and (3) to describe the strengths and weaknesses of the methods for the students. The study was done at English Department of UMS in 2011/2012 academic year. In this research, the data are derived from event, informant and document. There are three techniques in collecting data, namely: documentation, observation, and interview. The study shows that (1) the method used by lecturer is active learning. The lecturer also used some methods, namely wall poster, Jigsaw learning, and drilling. (2) the strengths of the methods used by the lecturer includes; the lecturer should be creative in transferring material to students, the lecturer can unearth the students' skills, and the lecturer has reference to the next teaching. The weaknesses of the methods used by the lecturer includes; the preparation of materials and the preparation of instructions. (3) the strengths of the methods for the students includes; students do not feel bored, students get experiences in teaching, students' motivation, increasing vocabulary. The weaknesses of the methods for the students are; reading class is a big class, students are uncomfortable in the big class, student and lecturer needs much time in the class. Conclusion, the use of active learning method on the teaching Reading at the second semester students of English Department of UMS are successful.